Heterogeneous Oceanic Arc Volcanic Rocks in the South Qilian Accretionary Belt (Qilian Orogen, NW China). (5th December 2018) - Yang, Liming; Song, Shuguang; Su, Li; Allen, Mark B; Niu, Yaoling; Zhang, Guibin; Zhang, Yuqi
Abstract: Primitive arc magmas in oceanic island arcs are probes of sub-arc magmatic processes and are crucial for understanding oceanic subduction. We report data for an Early Paleozoic oceanic arc volcanic complex in the Lajishan–Yongjing terrane, South Qilian Accretionary Belt (SQAB), Qilian Orogen, including zircon U–Pb dating and Hf–O isotopes, mineral and whole-rock geochemistry, and Sr–Nd isotope compositions. New zircon ages of ∼455–440 Ma constrain the timing of arc volcanism and the subduction of the Qilian Ocean. Based on petrography and bulk-rock composition, five lithological types have been identified: ankaramite; high-Mg basaltic andesite; high-Al andesite; boninite; sanukite. The volcanic sequence thus is one of the few island arcs where three types of near-primitive arc rocks including boninite, ankaramite and sanukite have been simultaneously produced. All these rocks have variably enriched Sr–Nd isotopic compositions, positive to slight negative zircon εHf ( t ) values and elevated zircon δ 18 O values. Boninites, ankaramites and sanukites are interpreted as contemporary near-primitive melts generated from different sources and conditions within an island arc setting. Boninites are characterized by low Ti and REE concentrations and high Cr# chrome spinel, and are interpreted as melts of refractory, Cpx-poor, spinel lherzolite or harzburgite at >25% partial melting. Anomalous zircon δ 18 O values of 6·57–7·61‰ and Sr–Nd mixing calculations suggest less than 2% incorporation of subducted oceanic sediments into the mantle source of the magmas. The ankaramites are characterized by low SiO2 and high MgO (Mg#), Cr, Ni and La/Yb ratios, and have similar isotopic ratios to tectonically adjacent ocean island basalt (OIB) lavas. The ankaramite lavas are likely to have derived from mantle sources similar to those of OIB; that is, pyroxenite-bearing garnet peridotite enriched in incompatible elements. High-Mg basaltic andesites and high-Al andesites may be derived from parental ankaramite magmas. Sr–Nd–Hf isotopic mixing modeling constrains the amount of silicic melt to ∼1–4% for ankaramite magma. Sanukites are of andesitic–dacitic composition with high Mg#, Cr and Ni, and enriched large ion lithophile elements and high La/Yb ratios. They are interpreted as having been generated by reaction of mantle peridotite with a silicic melt, itself derived from subducted sediments. Enriched Sr–Nd–Hf isotopic compositions constrain the amount of silicic melt to ∼10–15% for sanukite. Large compositional variations among the volcanic rocks from the same arc reflect heterogeneous mantle sources and variable degrees of mantle metasomatism by sediment-derived hydrous fluids or silicic melts, accompanied by secondary assimilation–fractional crystallization processes during magma ascent to the surface. The generation of the island arc volcanic sequence in the Lajishan–Yongjing Terrane is a response to the collision between the Lajishan–Yongjing Oceanic Plateau (recorded by the Lajishan–Yongjing Ophiolite) and the pre-existing trench–continental margin. Evolution from a continental margin in the North Qilian Accretionary Belt to an oceanic island arc in the SQAB records subduction advance and retreat in the history of the Qilian Ocean.